Metastatic melanoma treatment with checkpoint inhibitors in the COVID‐19 era: experience from an Italian Skin Cancer Unit. (4th June 2020) - Quaglino, P.; Fava, P.; Brizio, M.; Marra, E.; Rubatto, M.; Agostini, A.; Tonella, L.; Ribero, S.; Fierro, M. T.
Abstract : Linked articles: COVID‐19 SPECIAL FORUM. J Eur Acad Dermatol Venereol 2020; 34: e291–e310 .